Heart, lipids and hormones. Issue 4 (May 2017) - Wolf, Peter; Winhofer, Yvonne; Krššák, Martin; Krebs, Michael
Abstract : Cardiovascular disease is the leading cause of death in general population. Besides well-known risk factors such as hypertension, impaired glucose tolerance and dyslipidemia, growing evidence suggests that hormonal changes in various endocrine diseases also impact the cardiac morphology and function. Recent studies highlight the importance of ectopic intracellular myocardial and pericardial lipid deposition, since even slight changes of these fat depots are associated with alterations in cardiac performance. In this review, we overview the effects of hormones, including insulin, thyroid hormones, growth hormone and cortisol, on heart function, focusing on their impact on myocardial lipid metabolism, cardiac substrate utilization and ectopic lipid deposition, in order to highlight the important role of even subtle hormonal changes for heart function in various endocrine and metabolic diseases.